A Study on the Determination of Korea Affecting Tropical Cyclone Center for Best Tracking - Yumi Cha; Jinyeon Kim; Kiryong Kang; Nam-Young Kang; Won-Tae Yun (Advances in Meteorology)
The establishment of an independent tropical cyclone (TC) position is suggested for the purpose of constructing TC best track data of the Korea Meteorological Administration. The best track process was designed with five basic stages: database, potential interval (PI), optimization, smoothing, and metadata. The PI was newly devised as a tool for expressing the uncertainty in the location of the center of the TC. This PI determined the minimum range at which the center of the TC can be adjusted and based on the analysis manual for each dataset used in the TC best tracking. Furthermore, the PI can be optimized by the differential application of the range depending on the reliability of the data. By smoothing all TC centers within the optimized PI, a best track can be produced more stably. Therefore, the analysis can be less subjective even when the determination of the TC center is difficult. For three typhoon cases that had affected Korea in 2013 (LEEPI, KONG-REY, and DANAS), best tracks were obtained based on the suggested analysis stages and verified. The results showed that the PI was relatively large in the early development and weakening stage of the TC or when the estimation of the TC center was difficult because of interactions with the land. And the best tracking was performed well with reasonable applicability.